Uji Kandungan Fixed Carbon dan Volatile Matter Briket Arang Dengan Variasi Ukuran Partikel Serbuk Arang - Rany Puspita Dewi; Trisma Jaya Saputra; Sigit Joko Purnomo (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2020)
The utilization of biomass as an alternative to reduce dependence on fossil energy can be done through briquette technology. Through this technology, alternative energy sources can be obtained with high heating value and easy storage. The current promising source of biomass is sawdust and coconut shell waste because it is available in abundant quantities. This abundant amount has not been optimally used, because it only tends to be burned. Through briquette, technology is expected to increase the added value of waste. Briquette quality is influenced by several factors, one of which is the particle size of charcoal powder. The purpose of this study was to determine the effect of particle size of charcoal powder on the content of fixed carbon and volatile matter on charcoal briquettes. The research method was carried out by varying the particle size of charcoal powder, 10 mesh, 20 mesh, and 40 mesh. The research was carried out in several main stages, there are charcoal (carbonization), particle size reduction (grinding), sieving, mixing of raw materials, molding, drying, and testing of charcoal briquettes. The results showed that the charcoal briquettes produced had an average fixed carbon content of 58.761% and a volatile matter of 33.675% at 10 mesh charcoal powder particle sizes. At a particle size of 20 mesh, it produces charcoal briquettes with an average fixed carbon content of 60.491% and a volatile matter of 31.333%. While at 40 mesh, it produces charcoal briquettes with an average fixed carbon content of 59.216% and a volatile matter of 30.561%. The research results obtained further reinforce that the charcoal briquettes produced are feasible to be developed.